Clinical profile of patients presenting with gastrointestinal bleeding in a tertiary care hospital - Kumar, Chandan; Kumar Chakrabarti, Sumit; Chakraborty, Sucharita; Sinharay, Keshab (International Journal of Advances in Medicine, 2017)
Background: It has been seen that Upper gastrointestinal bleeding (UGIB) is one of the most mutual gastrointestinal emergencies for physicians and surgeons. In the recent past studies, there is raised incidence of peptic ulcer with raised frequency of bleeding from it. The range of upper GI bleeding fluctuates from region to region and relies on the status of the centre in hospital hierarchy. Methods: An observational, cross-sectional, hospital-based, single centre study was carried out on 150 patients admitted in tertiary care hospital with the presentation of GI bleeding. A detailed patient history was taken followed by required clinical and laboratory investigations. Then patients were resuscitated and subjected to endoscopic procedure. Results: 150 patients were treated among which 105 were male (70%) and 45 females (30%). 111 patients (74%) had upper GI bleed, 28 patients (19%) had lower GI bleed, and 11 patients (7%) had obscure bleed. 41% of the population were diagnosed to have peptic ulcer (gastric or duodenal) as the cause behind GI bleed forming the main aetiology in this study population, 26% had oesophageal varices constituting second important cause of GI bleed, and 7% had obscure bleed. Those who had undergone UGI endoscopy or sigmoidoscopy or colonoscopy within last one month and who were having GI bleed following GI surgery were excluded from the study. Conclusions: It was seen that upper GI bleeding is more common than lower GI bleeding. Peptic ulcer was the chief cause resulting in gastrointestinal bleed followed by oesophageal varices. Gastrointestinal bleeding was more common in male population affecting mainly subjects over 40 years of age.